2018
DOI: 10.1111/jir.12572
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation of adults with Down syndrome: lesson from a 10‐year experience from a community hospital

Abstract: Background Life expectancy of individuals with Down syndrome (DS) has improved significantly over the past decades. However, there are sparse data documenting the co‐morbidities and hospitalisation of adult patients with DS in the literature. The aim of this study was to characterise the co‐morbidities and pattern of hospitalisation in adult patients with DS during a 10‐year period at the community hospital as well as to compare hospitalisation parameters with the general adult population during the same years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
4
13
1
Order By: Relevance
“…However, men had fewer visits to outpatient health care visit and fewer planned visits than women. This result is not consistent with the few previous studies that have reported differences between men and women with DS using health care such as one study that report longer stay in hospitals for men compared with women with DS [ 19 , 28 ] and slightly more hospital admissions [ 28 ]. However, the previous studies included people at younger ages and no outpatient data.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…However, men had fewer visits to outpatient health care visit and fewer planned visits than women. This result is not consistent with the few previous studies that have reported differences between men and women with DS using health care such as one study that report longer stay in hospitals for men compared with women with DS [ 19 , 28 ] and slightly more hospital admissions [ 28 ]. However, the previous studies included people at younger ages and no outpatient data.…”
Section: Discussioncontrasting
confidence: 95%
“…with women with DS [19,28] and slightly more hospital admissions [28]. However, the previous studies included people at younger ages and no outpatient data.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, studies have only recently begun to focus on the adult DS population with respect to their rate of infections, and the number and length of hospitalizations. In general, hospitalization rate is higher in adults with DS compared with the general population due to pneumonia or aspiration (60)(61)(62). Tenenbaum and colleagues analyzed 297 hospitalizations of 120 adults with DS (aged 18-73 years in medical centers in Israel between 1988-2007) and compared these data with a control population.…”
Section: Infectious Diseases In Ds: Hospitalization Rate and Lengthmentioning
confidence: 99%